2014
DOI: 10.4174/astr.2014.87.3.118
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of sentinel lymph node mapping in colon cancer:in vivovs.ex vivotechniques

Abstract: PurposeClinical usefulness of sentinel lymph node (SLN) mapping in colorectal cancer remains controversial. The aim of this study is to evaluate the accuracy of the SLN mapping technique using serial sectioning, and to compare the results between ex vivo and in vivo techniques.MethodsFrom February 2011 to October 2012, 34 colon cancer patients underwent SLN mapping during surgical resection. Eleven patients were analyzed with the in vivo method, and 23 patients with the ex vivo method. Patient characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…15,16 Recently, SLN mapping has been tried to facilitate ELND and to improve stating accuracy in CC. 12,13,14,17 However, notwithstanding our results, the feasibility of SLN in CC seems to be controversial and still remains to be defined. Hence, this study was planned.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…15,16 Recently, SLN mapping has been tried to facilitate ELND and to improve stating accuracy in CC. 12,13,14,17 However, notwithstanding our results, the feasibility of SLN in CC seems to be controversial and still remains to be defined. Hence, this study was planned.…”
Section: Discussionmentioning
confidence: 77%
“…Lymph node status in CC is a major prognostic factor that determines the disease recurrence, survival, and the adjuvant treatment. 8,11,12,13,14 Disease recurrence still remains the most important problem after radical surgery likely due to inadequate lymph node dissection. The optimal number of LN required to accurately predicting lymph node negativity has been a point of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ICG-FI is not influenced by the patient's BMI nor by lymphatic invasion, as has been shown for conventional methods, and has been shown to increase SLN detection in comparison with standard techniques (16,18). Although the ex vivo blue dye technique in SLN detection in CRC is well documented in the literature and has been demonstrated to be as effective and sensitive as the in vivo technique (19,20), no study has yet evaluated the role of ICG-FI using the ex vivo technique for SLN detection.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy percent of included patients had pT3-4 tumors. This could cause a higher risk of missed metastases due to lymphatic channel blockages (20). This is problematic as these patients are probably the most at-risk for developing further metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…24 Further studies failed to improve a great deal on these results with large variations in the reported detection rates, sensitivity and false-negative rates, which have been variously attributed to heterogeneity in detection techniques, definition of the SLN, time interval between injection and SLN detection, histopathological techniques, and patient characteristics, including tumour stage and body mass index. 25 A recent meta-analysis showed a SLN identification rate of 92% with a pooled sensitivity rate for detecting LN metastases of 69.6% (range 33.3-100%) and a false-negative rate of 30.4%. 26 Importantly, concerns have been expressed regarding the high false-negative rates and whether metastases from colon cancer follow an orderly spread through tiers of LNs, or rather metastasise as skip lesions.…”
Section: Sentinel Lymph Node Mappingmentioning
confidence: 99%